Dyadic effects of cognitive function on depressive symptoms among middle‐aged and older Chinese couples. (8th April 2023) - Li, Yujin; Wu, Qi; Guo, Lizhi; Weerawardena, Nethmi Sulakna; Luo, Fengping; Yu, Bin
Abstract: Background: Although cognitive function and depressive symptoms have been suggested to be closely related, less attention has been paid to this association within married couples. This study explored the reciprocal dyadic relationship between cognitive function and depressive symptoms over time. Methods: This study used four waves of data from the China Health and Retirement Longitudinal Study and analyses were restricted to middle‐aged and older couples aged 45 or older. Actor‐partner interdependence model adjusted for confounding factors was employed to examine the reciprocal association between cognitive function and depressive symptoms at both the individual and couple levels. Measures of cognitive function consisted of episodic memory and mental status. Depressive symptoms were measured by the Center for Epidemiological Studies Depression scale. Results: For both husbands and wives, cognitive function was reciprocally associated with depressive symptoms at the individual level. Spouses' lower cognitive function was significantly linked to their partners' greater depressive symptoms. However, ones' depressive symptoms were not related to their partners' cognitive function. Conclusions: These findings expand our knowledge about the dyadic relationship between cognitive function and depressive symptoms in Chinese couples. Effects of interventions for depression in middle‐aged and older adults may be enhanced by considering the marital context. Key points: Cognitive function and depressive symptoms were reciprocally related at the individual level among middle‐aged and older Chinese couples. Partner effects were found. One spouse's lower cognitive function at baseline was significantly associated with the other's greater depressive symptoms.